Evaluation of a change in cytomegalovirus prevention strategy following pediatric solid organ transplantation. Issue 2 (30th December 2019) - Pangonis, Scott; Paulsen, Grant; Andersen, Heidi; Flores, Francisco; Miethke, Alexander; Peters, Anna; Kocoshis, Samuel; Lazear, Danielle; Garr, BreAnn; Schecter, Marc; Chin, Clifford; Hemmelgarn, Trina; et al.
Abstract: Background: An optimal cytomegalovirus (CMV) prevention strategy following solid organ transplantation (SOT) remains uncertain. This study reports on the rates of CMV events following a change in a local prevention guideline involving increased surveillance, earlier transition to oral valganciclovir, and decreased CMV‐immunoglobulin use. Methods: A retrospective cohort study utilizing historical controls evaluated the rates of CMV invasive disease pre‐ and post‐intervention among pediatric heart, liver, and kidney recipients. Outcomes were recorded for the 4 years pre‐ and post‐intervention, 9/2009‐10/2017. Logistic regression was used to estimate the risk of a CMV event. Results: There was no difference in the rates of CMV invasive disease between the two study groups ( P  = 1). An increase in the detection of CMV events occurred ( P  = .04), predominantly asymptomatic CMV infection. This increase was independently associated with increased surveillance testing among high‐risk heart and liver recipients, aOR 1.08 (1.06‐1.12). Surprisingly, 28.9% of CMV events occurred during antiviral prophylaxis. Conclusions: Modification of the local CMV prevention guideline did not result in an increase in CMV invasive disease. CMV events occurred while on prophylaxis, highlighting a potential difference from adult solid organ transplant (SOT) and emphasizing the potential need for monitoring on prophylaxis in the pediatric population.